Makna Tari Bongbang dalam Tradisi Ruwat Desa di Desa Golat Kabupaten Ciamis - Siska Febriani; Asti Tri Lestari; Wan Ridwan Husen (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to analyze one of the traditional arts, namely the Bongbang dance in the Ruwat Desa tradition. The problem raised in this research is the meaning of the Bongbang dance. This research uses a qualitative method with a semiotic approach, namely the researcher tries to find or analyze symbols or signs in the text systematically. The data collection techniques used were observation, interviews and documentation. The results of this research show that the Bongbang dance has four songs, namely Papalayon, Deungkleung, Jaging and Renggong Buyut. Each of these songs has meaning from the sources of everyday life. The meaning of the Bongbang dance can be seen from its movements, namely when the hand is raised with five fingers, indicating that there are five pillars of Islam and the hand is raised with one finger, indicating that God is One.